International Airport of Sentani, Papua (with Green & Sustainable Architecture Approach) - Sadewa, Rilo Alief; , Wisnu Setiawan, ST., M.Arch.,Ph.D (2017)
Means of transportation and buildings ranked as the second and third worst destructive factors of nature due to human activities, where the first position is occupied by coal and diesel power plant (Natural Resources Defense Council (NRDC), 2005). Indonesia which is touted as the lungs of the world is required to be sensitive and responsive to environmental problems. Papua as one among the largest provinces in Indonesia has shortcomings in terms of infrastructure to facilitate the activities of aviation. Based on elucidation of the background of the study, an environmentally friendly international airport design based on standardized green and sustainable principle is required. In order to realize the design in the best possible result, proper basic analysis is conducted based on data of Jayapura region obtained from field survey in the early stage of the design. The first step of the analysis is to determine an appropriate location as the site for further development of the design. Then, analysis of the chosen site which includes analysis of accessibility, topography, hydrology, vegetation, sun, wind, view, circulation, weather and zone. From the results of these basic analysis, green & sustainable concept is applied in accordance to aspects and standards issued by legal entities which dedicated to the cause. This is done to maximize the efficiency and effectivity of the fundamental concept. In order to complement the sophistication of the technology intended for the green and sustainable concept, architectural concept which is chosen for the design is futuristic style. The last step, is performing an assessment of space and room as well as the area of each item to determine the connection of each individual space to the other. Keywords: International Airport, Papua, Green, Sustainable, Environment